A REVISION OF MALESIAN ISACHNE SECT. ISACHNE (GRAMINEAE, PANICOIDEAE, ISACHNEAE) - Eka AP Iskandar; Jan Frits Veldkamp (Research Center for Biology, 2004)
ISKANDAR, E.A.P. & VELDKAMP, J.F. 2004. A revision of Malesian Isachne sect. Isachne (Gramineae, Panicoideae, Isachneae). Reinwardtia 12 (2): 159 – 179. – There are ca. 23 species of Isachne in Malesia of which the seven belonging to sect. Isachne are treated here. Isachne miliacea Roth has been misapplied to I. minutula (Gaudich.) Kunth, as its type belongs to I. globosa (Thunb.) Kuntze. Isachne pulchella Roth is the correct name for I. dispar Trin.